Experiential Codes for Opportunity Identification in Sustainable Entrepreneurship (Third Sector Social Economic Review, 2026)
Sustainable entrepreneurship, a multidimensional entrepreneurial approach aimed at generating innovative solutions to environmental and social problems, has attracted increasing academic and practical interest in recent years. However, the literature has only limited coverage of how sustainable entrepreneurs identify opportunities and what advice they offer to potential sustainable entrepreneurs based on their experiences in this process. This study aims to reveal how sustainable entrepreneurship opportunities are defined based on the experiences of sustainable entrepreneurs who implement sustainable business models and to present recommendations for potential entrepreneurs entering this new field of business. The study was designed within a qualitative research approach, and data were collected through semi-structured interviews with 16 sustainable entrepreneurs operating in different sectors. The interview data were examined using thematic analysis, and the analysis process was conducted using MAXQDA 24 Pro software. The findings show that the recommendations of sustainable entrepreneurs are concentrated around five main themes: market-product and visibility strategy, learning and competency development, access to resources and support, implementation discipline and resilience, and sustainability and ethical responsibility. The study reveals that sustainable entrepreneurship opportunities are shaped not only by individual values or intentions but also by the holistic interaction of market knowledge, learning processes, resource management, and ethical responsibility. In this respect, the research offers an original, experience-based, and practice-oriented contribution to the sustainable entrepreneurship literature.
Keywords: Opportunity Identification; Entrepreneurship; Sustainable Enterprise; Sustainable Entrepreneurship; Sustainable Entrepreneurship Opportunities